Orientation effects of curved finned cylinders under natural convection - Kim, Donghyuk; Kim, Dong Kwon (Journal of Mechanical Science and Technology, 2025)
This study presents a comprehensive experimental investigation on the thermal performance of curved finned cylinders under natural convection at various inclination angles. Experiments were conducted to measure heat transfer rates from curved finned cylinders with different numbers of fins (8, 12, 24, and 48) at inclination angles of 30°, 45°, and 60°. Based on the experimental results, a novel correlation for predicting the Nusselt number of curved finned cylinders was developed, which accurately accounts for the effects of inclination angle, fin number, and Rayleigh number. The results demonstrate that optimal thermal performance improves significantly with increasing inclination angle. An optimal fin number that minimizes thermal resistance was identified, which remains nearly constant across all inclination angles. In addition, it is demonstrated that the optimal fin thickness increases as the inclination angle increases.
Keywords: Curved plate fin; Curved plates; Experimental investigations; Fin numbers; Finned cylinder; Heat transfer rate; Inclination angles; Orientation effect; Plate fins; Thermal Performance; Curved plate fins; Finned cylinders; Natural convection; Orientation effects